Impact of Bank Cards Transactions on Banking Fee Income Growth in Russia - Markova, Olga M.; Rudakova, Olga S.; Martinenko, Nadezhda N. (Journal of Reviews on Global Economics, 2018)
The article covers the advent of new sources of income which banks should concentrate on in the light of digitalization and development of new technologies. In spite of dynamic bank cards market development, there are many unresolved issues and challenges in this sphere, which generally relate to the necessity to enhance legal framework regulation; development of effective anti-fraud methods; utilization of innovative technologies and others. The Russian economy and society are in need of highly efficient, safe and economically viable and independent payment system, including such method of payments as bank cards. The conducted analysis revealed that there is a correlation between individual indicators of the bank card market development and the level of a bank's income. The latter depends not only on the revenue flows generated by the growth of interest rates on loans or other conventional types of banking transactions, but on the level of bank cards transactions. It is important to identify correlation between the growth of banks' fee income from card transaction and the amount of funds raised by commercial banks, the numbers of ATM, the average income per card, the number of operating cards, and per capita income of the population.